Restoring shellfish reefs: Global guidelines for practitioners and scientists - James A. Fitzsimons (Conservation Science and Practice, 2020)
Abstract Widespread global declines in shellfish reefs (ecosystem‐forming bivalves such as oysters and mussels) have led to growing interest in their restoration and protection. With restoration projects now occurring on four continents and in at least seven countries, global restoration guidelines for these ecosystems have been developed based on experience over the past two decades. The following key elements of the guidelines are outlined: (a) the case for shellfish reef restoration and securing financial resources; (b) planning, feasibility, and goal setting; (c) biosecurity and permitting; (d) restoration in practice; (e) scaling up from pilot to larger scale restoration, (f) monitoring, (g) restoration beyond oyster reefs (specifically mussels), and (h) successful communication for shellfish reef restoration projects.